ANALISA STRUKTUR MIKRO TERHADAP PADUAN AL-CU HYPEREUTEKTIK - Ismail, Ismail; Surya Wijaya, Adhi (MEKANIKA: Jurnal Teknik Mesin, 2016)
The cooling rate of the material with a permanent mold of its cooling rate begins on the mold walltowards theinner or middle of the mold. This study analyzes the temperature of casting and moldtemperature which must have an effect on the existing structure of the material. Hyperutectic aluminumalloys are aluminum and copper alloys with eutectic phases which have the advantage of melting andpouring (especially around the eutectic region) at 548 ° C. The foundry used is gravity casting usingpermanent mold that is easy to dismantle. Starting from the process of composition of Aluminum andCooper according to Cu eutectic point of 32.7%, here Cooper composition is more dominant than Al-Cu hypoeutectic composition. Pouring temperature 600 ° C, 650 ° C, and 700 ° C as the first variationwhile room temperature temperature temperature, 100 ° C, and 200 ° C as the second variation. At thetime of the process the specimen cut is divided into A, B, and A '' codes. The influence of the pouringtemperature and the temperature of the mold affects the microstructure formed. The higher the pouringtemperature, the more clearly visible the structure, is clearly visible at the pouring temperature of 700° C while the smaller the mold temperature the rougher the structure, the more outward the direction ofthe structure, and it can be said that a dendrite is formed. Codefication B can be called the core or themidpoint of the mold is the furthest point from the cooling rate process, the structure contained in theB-code is clear, bold and coincident.